IMPLEMENTASI PROGRAM BANTUAN RUMAH SEDERHANA LAYAK HUNI DI KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Mulyady, Mus; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Simple habitable Home Support Program RLH is a program aimed at eradicating poverty through the development of habitable homes for poor people who still have uninhabitable houses intended to improve and provide basic community infrastructure needs in kepenghuluan / kelurahan, implemented through empowerment patterns the community of the downstream rokan district program which is poured into regent 19 of 2014 as a guideline in the implementation of development, the local community is an important actor in the implementation of this program.The purpose of this study is to understand Imaplementasi Simple humble home support program in sub-district of Babusallam district rokan hilir district. Theoretical concepts used by researchers are the factors that influence the implementation of policies used by George Edward III where the indicators used are communication, resources, disposition and bureaucratic structure. This research uses descriptive qualitative method, using interview technique, observation and documentation.the results showed implementation of housing programs habitable home has not run well, the implementation of the do still many that are not in accordance with existing guidelines such as community involvement in this program is not maximal. Meanwhile, the inhibiting factors in the implementation of the Simple Habitable Home subsidy program are the inaccuracy of the target, the lack of community participation and the sustainability of the programKeywords: Policy Implementation, community-based self-development, Simple Habitable House